Blue print report auto vision (AV) optical centre / Anis Nur Izzati Syaffrizal - Syaffrizal, Anis Nur Izzati (2020)
Auto Vision (AV) Optical Centre is a sole proprietorship business, has new product to introduce to the consumers which is Auto Focus glasses. My business decided to supply glasses since it parallels with consumers‟ demand whose had short-sightedness and long- sightedness at the same time. Auto Focus glasses is a liquid based lenses made up of glycerine, a thick clear liquid, enclosed in flexible membranes. The liquid lenses change shape according to the distance of objects, making reading glasses and ifocals unnecessary.Overall marketing strategy will be included specific marketing philosophy and strategy of the business, the value chain and the channel of distribution in the target market. Firstly, AV Optical Centre‟s target market will be based on the residence in Johor Bahru area since the business is located in the middle city of Johor Bahru. For initial intensive selling effort, my business has set the target customers in other words, types of customer groups that will buy my product. This business is targeting presbyopia (aging people with loss focusing ability) and young people with faulty eyes highly caused by genes inherited from family.